Utilization of Biduri Juice (Calotropis gigantea) in The Process of Buffalo Milk Coagulation on Quality of Soft Cheese - Bulkaini Bulkaini; B.R.D. Wulandani; IN.S. Miwada; Twenfosel O. Dami Dato; Liana Dewi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2020)
Cheese is a processed product with a basic ingredient in the form of milk which is produced by separating solid substances in milk through a coagulation process. Soft cheese is cheese with a moisture content of 45-80%. Research aims to know the benefits of biduri juice in the manufacture of buffalo milk soft cheese. In an effort to determine the benefits of the biduri juice an experimental method was carried out using a Randomized Block Design (RBD).The study consisted of two groups, namely K1 which was made of cheese using 0.02 ml / 2 liter of rennet milk, while K2 was made of cheese using 0.6 cc/2 liter of biduri sap milk. The cheese produced on K1 and K2 was stored for 0 days, 12 days and 24 days as treatment. The results of the study which consisted of protein, fat and water levels were analyzed using analysis of variance based on a Randomized Block Design (RBD) using the SPSS version 16 program and continued with the Duncant test with a confidence level of 5%. The results showed that the use of biduri juice 0.6 cc/2 liters of milk in cheese making produced cheese with protein content ranging from 22.74-23.85% higher than the use of rennet at 21.99-23.65%. Fat content of cheese with biduri juice coagulation resulted in fat content ranging from 0.59-0.84% lower than using rennet ranging from 0.8-1.04%. The water content of soft cheese coagulated with biduri juice and rennet is still in the normal range of water content set by the United States Department of Agriculture (USDA), which is not more than 80%. Based on the results of the study, it can be concluded that the use of biduri juice at the level of 0.6 cc / 2 liters of fresh buffalo milk in making soft cheese with a storage time of 0 days, 12 days and 24 days, it can produce protein and fat content of soft cheese that meets SNI with water content of cheese according to USDA standards, namely not exceeding 80%.